2021
DOI: 10.1177/00938548211036177
|View full text |Cite
|
Sign up to set email alerts
|

Linking Organizational Justice to Organizational Commitment Among Nigerian Police Officers

Abstract: Organizational commitment is an imperative aspect of occupational attitudes as it signals employees’ willingness to stay with their organization and effectively achieve collective goals. Although recent studies have assessed factors influencing police officers’ organizational commitment, very little is known about the antecedents of police commitment in African countries. Based on a survey of Nigerian police officers, the study assesses the linkage between organizational justice and organizational commitment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…One of the basic ideas in the theory is that people establish a fairness strategy before they're even exposed with and just evidence, and that once formed, this reasoning is difficult to change. This initial step establishes a fairness criteria depending on the first particular justice seen while also establishing a general fairness approach (Sun et al, 2022). This shows that the earliest information needed has the biggest impact on overall fairness perceptions, resulting in a baseline condition.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the basic ideas in the theory is that people establish a fairness strategy before they're even exposed with and just evidence, and that once formed, this reasoning is difficult to change. This initial step establishes a fairness criteria depending on the first particular justice seen while also establishing a general fairness approach (Sun et al, 2022). This shows that the earliest information needed has the biggest impact on overall fairness perceptions, resulting in a baseline condition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The emphasis on digital disparity overlooks the enormous role of social media in reshaping the labor industry's layout and reshaping the environment in which job seekers and businesses perceive. Sun et al (2022), demonstrates how job application portal create new online "settings" in which employees exhibit oneself to hiring managers, and how its characteristics serve as "furniture, de'cor, physical layout, and other background elements" for job seeker activities (Lin & Wang, 2020;Roch et al, 2019). People's desires to work for a company are influenced considerably by their opinions of the firm's social performance, which sends a positive signal to the company's stakeholders, including customers, owners, and job candidates (Guzzo et al, 2022).…”
Section: Job Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…A small body of studies has found that organizational fairness may be linked to officer organizational commitment (Crow et al, 2012;Farmer et al, 2003;Frank et al, 2020;Qureshi et al, 2017;Rosenbaum and McCarty, 2017;Sun et al, 2022). Police are a critical part of the justice system (Frank et al, 2020;Qureshi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%